2010
DOI: 10.1042/bst0380422
|View full text |Cite
|
Sign up to set email alerts
|

Ancient machinery embedded in the contemporary ribosome

Abstract: Structural analysis, supported by biochemical, mutagenesis and computational evidence, indicates that the peptidyltransferase centre of the contemporary ribosome is a universal symmetrical pocket composed solely of rRNA. This pocket seems to be a relic of the proto-ribosome, an ancient ribozyme, which was a dimeric RNA assembly formed from self-folded RNA chains of identical, similar or different sequences. This could have occurred spontaneously by gene duplication or gene fusion. This pocket-like entity was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 52 publications
4
49
0
2
Order By: Relevance
“…There is a consensus that some parts of the ribosome are even older than LUCA, predating the protein world. Parts of Domain V of the 23S rRNA are believed to be among the most ancient parts of the ribosome (Woese 2001;Wolf and Koonin 2007;Smith et al 2008;Bokov and Steinberg 2009;Belousoff et al 2010;Fox 2010) while Domain III is thought to be a more recent addition (Hury et al 2006). The data presented here support the hypothesis that Domain III was added as an intact entity to the ancestral ribosome-assuming that the 3D domain is a unit of ribosomal evolution.…”
Section: Evolutionary Implications Of the Domain Structure Of The Domsupporting
confidence: 77%
See 2 more Smart Citations
“…There is a consensus that some parts of the ribosome are even older than LUCA, predating the protein world. Parts of Domain V of the 23S rRNA are believed to be among the most ancient parts of the ribosome (Woese 2001;Wolf and Koonin 2007;Smith et al 2008;Bokov and Steinberg 2009;Belousoff et al 2010;Fox 2010) while Domain III is thought to be a more recent addition (Hury et al 2006). The data presented here support the hypothesis that Domain III was added as an intact entity to the ancestral ribosome-assuming that the 3D domain is a unit of ribosomal evolution.…”
Section: Evolutionary Implications Of the Domain Structure Of The Domsupporting
confidence: 77%
“…The ribosome in its present form was well-established at the emergence of the last universal common ancestor of life (LUCA) (Woese 2001;Wolf and Koonin 2007;Smith et al 2008;Bokov and Steinberg 2009;Belousoff et al 2010;Fox 2010). There is a consensus that some parts of the ribosome are even older than LUCA, predating the protein world.…”
Section: Evolutionary Implications Of the Domain Structure Of The Dommentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative effect of the first four initial expansions (Fig. 5) gives a structure that is strikingly similar to an ancestral PTC proposed independently by Yonath and coworkers (30,31). Those investigators suggested rRNA components of the PTC as an ancient catalytic heart of the common core.…”
mentioning
confidence: 75%
“…It is composed exclusively of RNA and has twofold symmetry formed by rRNA domain V (Bashan et al 2003). The extremely high degree of sequence and structural conservation of this region has engendered the proposition that this region constitutes the ''proto-ribosome'' (for review, see Polacek and Mankin 2005;Davidovich et al 2009;Belousoff et al 2010;Fox 2010). Moreover, in vitro experiments selecting for the ribozymes capable of transpeptidation selected sequences that resembled the PTC (Zhang and Cech 1997).…”
Section: Discussionmentioning
confidence: 99%